Cubine Monolayer as a Super Sensor for NO2 Molecule Detection and Capture. Issue 5 (12th February 2022) - Lin, Jiayang; Yang, Dongdong; Huang, Shiming; Chen, Xin; Wang, Xianglong; Zhang, Yifan; Xiao, Beibei; Jiang, Xiaobao
Abstract: In this work, the potential application of cubine monolayer as a highly sensitive sensor for the detection and capture of toxic gas molecule NO2 is investigated by employing density functional theory (DFT) calculations. Eight gas molecules, namely CO, CO2, CH4, H2 S, SO2, NH3, NO, and NO2 are considered. After examining the adsorption energy, adsorption distance, variation of bond length and Mulliken charge, the results show that only NO2 molecule present chemical adsorption on cubine monolayer. The calculated work functions and I – V curves indicate that cubine has the highest sensitivity to NO2 molecules. The adsorption energies decrease following the increase of strain in both A and B directions, when the strain along the A direction reaches 12%, the adsorption energy decreases to −0.686 eV, which shows physical adsorption. This provides a desorption strategy for recycling. The calculations employed in this work indicate that the cubine monolayer can be a prominent candidate for the application of a super sensor to detect and capture NO2 toxic gas molecules. Abstract : In this work, the application of cubine monolayer is explored as sensing materials for the detection and capture of toxic gas molecules NO2 using density functional theory. The adsorption of eight toxic gas molecules, CO, CO2, CH4, SO2, H2 S, NH3, NO, and NO2 are calculated and found that cubine monolayers have excellent selectivity and sensitivity to NO2 molecules.